2009
DOI: 10.1080/10641960802668714
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Losartan and Hydrochlorothiazide in Human Plasma by LC/MS/MS with Electrospray Ionization and Its Application to Pharmacokinetics

Abstract: A method based on a simple liquid-liquid extraction (LLE) followed by high-performance liquid chromatography with negative ion electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) detection was developed for the simultaneous determination of losartan (LOS) and hydrochlorothiazide (HCTZ) in human plasma, using valsartan (VAL) and chlorthalidone (CHTD) as an internal standard, respectively. The acquisition was performed in multiple reactions monitoring (MRM) and the limit of quantification was 4 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…Plasma concentrations of losartan and losartan acid (LA) were determined by LC-MS/MS. Salvadori et al [43] developed a method based on a simple liquid-liquid extraction (LLE) followed by HPLC with negative ion ESI tandem mass spectrometry (HPLC-ESI-MS/MS) detection for the simultaneous determination of losartan (LOS) and hydrochlorothiazide (HCTZ) in human plasma, using valsartan (VAL) and chlorthalidone (CHTD) as an IS, respectively. The acquisition was performed in multiple reaction monitoring (MRM) and the limit of quantification was 4 ng/mL for both LOS and HCTZ.…”
Section: Hplc-mass Spectrometrymentioning
confidence: 99%
“…Plasma concentrations of losartan and losartan acid (LA) were determined by LC-MS/MS. Salvadori et al [43] developed a method based on a simple liquid-liquid extraction (LLE) followed by HPLC with negative ion ESI tandem mass spectrometry (HPLC-ESI-MS/MS) detection for the simultaneous determination of losartan (LOS) and hydrochlorothiazide (HCTZ) in human plasma, using valsartan (VAL) and chlorthalidone (CHTD) as an IS, respectively. The acquisition was performed in multiple reaction monitoring (MRM) and the limit of quantification was 4 ng/mL for both LOS and HCTZ.…”
Section: Hplc-mass Spectrometrymentioning
confidence: 99%
“…Also, the run time of the method was only 2.4 min with the use of UPLC, which further increased the throughput. Various methods are reported in literature for the quantitation of amodiaquine (Stepniewska et al 2009), chloroquine (Hodel et al 2009;Singhal et al 2007) and chlorthalidone (Khuroo et al 2008;Salvadori et al 2009) in plasma. However, all the reported methods use time and resource-intensive extraction methods or have a long run time.…”
Section: Discussionmentioning
confidence: 99%
“…Losartan should be administered orally once or twice daily for a total daily dose of 25-100 mg. 3 Last studies showed that several HPLC ,LC/MS/MS methods were used for determination of losartan and its metabolite in human plasma. [4][5][6][7][8][9][10][11][12] The aim of this study was to develop a simple, rapid sensitive and reliable HPLC method with Ultraviolent detection for quantization of losartan in human plasma samples and to compare the bioavailability of two losartan tablets (50 mg) formulations (losartan from Iranian company, as a test formulation and COZAR, MSD ,The Netherlands as a reference formulation) . The method was validated according to procedures and acceptance criteria based on FDA guideline and recommendations of ICH, to provide enough selectivity, sensitivity and reliability in pharmacokinetic and bioequivalence studies.…”
Section: Introductionmentioning
confidence: 99%